2013
DOI: 10.4067/s0716-97602013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the rate of drying reduces metabolic imbalance, lipid peroxidation and critical water content in radicles of garden pea (Pisum sativum L.)

Abstract: Orthodox seeds become desiccation-sensitive as they undergo germination. As a result, germinating seeds serve as a model to study desiccation sensitivity in plant tissues. The eff ects of the rate of drying on the viability, respiratory metabolism and free radical processes were thus studied during dehydration and wet storage of radicles of Pisum sativum. For both drying regimes desiccation could be described by exponential and inverse modifi ed functions. Viability, as assessed by germination capacity and tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The role of free radical activity in seed deterioration in germinating orthodox and recalcitrant seeds as a result of drying has been supported by evidence from studies over a period of two decades [3][4][5][6][7][8][9][10]. Berjak and Pammenter [11] suggested that the recent interest may be a result of implication of (re)active oxygen species (ROS and/or AOS) in an intracellular signaling network.…”
Section: Introductionmentioning
confidence: 84%
“…The role of free radical activity in seed deterioration in germinating orthodox and recalcitrant seeds as a result of drying has been supported by evidence from studies over a period of two decades [3][4][5][6][7][8][9][10]. Berjak and Pammenter [11] suggested that the recent interest may be a result of implication of (re)active oxygen species (ROS and/or AOS) in an intracellular signaling network.…”
Section: Introductionmentioning
confidence: 84%
“…2a), Li and Sun (1999) and Parkhey et al (2012) also perceived increased accumulation of ⋅ O 2 − during storage/ desiccation of seeds. During RD, radicles were exposed for a while towards stress condition, hence resulted in low levels of ⋅ O 2 − (Ntuli et al 2013). In contrast, during both SD and WS, it was overproduced chiefly due to age related imbalance in cellular metabolism and not desiccation (Wesley-Smith et al 2001;Berjak and Pammenter 2008).…”
Section: Discussionmentioning
confidence: 99%
“…components, was considered as one of the potent requirements conferring DT to seeds (Berjak and Pammenter 2008). However, above protective system might become impaired during desiccation or hydrated storage and certainly are inefficient in removal of ROS, resulting oxidative injury in seed tissues (Chaitanya and Naithani 1994;Ntuli et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations